Historestorative effects of Warbugia ugandensis on high fat diet induced atherosclerosis in New Zealand rabbits - O. Oyugi, Spencer; Allan, Khisa W.; M. Nyabola, Atanas (International Journal of Research in Medical Sciences, 2024)
Background: Historestorative feature is a vital component that any organ can acquire secondary to its damage. Most of the time damage arises from traumatic injury or toxification by toxic agents. In the current context the aortic intima lumen significantly histologically changed secondary to administration of Warbugia ugandensis thus increasing blood supply to vital organs. Methods: Posttest only true experimental study design was used with 33 male New Zeeland rabbits considered for this study. In grouping of animals, Systematic sampling method was used to assign them as control and experimental groups. W. ugandensis extract was obtained after which phytochemical analysis and acute oral toxicity were conducted to determine safe dose. The animals were fed on high fat diet to induce atherosclerosis. Results: The mean fraction of restorative group reduced significantly (p=0.0001) relative to vehicle control group. There was no significant difference in mean area fraction of W. ugandensis restorative group when compared with negative control group (p=1.000). On histological features, restorative group had a smaller lesion as compared to vehicle group. The lipid core was smaller in size with large fibrous cap around it. The endothelial cells surrounded the lesion as opposed to vehicle control group make it more stable. Conclusions: Therefore, it can be concluded that W. ugandensis has historestorative benefits portrayed by reduction of atherosclerotic lesion with a lipid core covered by a large fibrous cap.